2018
DOI: 10.5194/angeo-36-415-2018
|View full text |Cite
|
Sign up to set email alerts
|

A major event of Antarctic ozone hole influence in southern Brazil in October 2016: an analysis of tropospheric and stratospheric dynamics

Abstract: Abstract. The Antarctic ozone hole is a cyclical phenomenon that occurs during the austral spring where there is a large decrease in ozone content in the Antarctic region. Ozone-poor air mass can be released and leave through the Antarctic ozone hole, thus reaching midlatitude regions. This phenomenon is known as the secondary effect of the Antarctic ozone hole. The objective of this study is to show how tropospheric and stratospheric dynamics behaved during the occurrence of this event. The ozone-poor air mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 23 publications
2
16
0
3
Order By: Relevance
“…The MWR-MLS inter-comparison at 27 km reveals a MBE of 5 %, which is consistent with the value obtained by Ohyama et al (2016). Boyd et al (2007) also carried out similar inter-comparisons between MLS and two MWRs installed in Mauna Loa, Hawaii, and Lauder, New Zealand. The differences reported for Lauder range from +7 % to 10 % between ∼ 20 and ∼ 28 km, while for Mauna Loa differences are around ∼ 3 % (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The MWR-MLS inter-comparison at 27 km reveals a MBE of 5 %, which is consistent with the value obtained by Ohyama et al (2016). Boyd et al (2007) also carried out similar inter-comparisons between MLS and two MWRs installed in Mauna Loa, Hawaii, and Lauder, New Zealand. The differences reported for Lauder range from +7 % to 10 % between ∼ 20 and ∼ 28 km, while for Mauna Loa differences are around ∼ 3 % (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…For this analysis, one needs to consider the previous days of the event or equatorial origin when a decrease in absolute potential vorticity occurs (Semane et al, 2006). Bittencourt et al (2018) and Bresciani et al (2018) showed the analysis of an extreme event of influence of the AOH on regions of middle latitudes through the analysis of the stratospheric dynamics with the fields of PV.…”
Section: Identification Of Aoh Influence Eventsmentioning
confidence: 99%
“…When there is an increase in the APV it can be stated that the mass of air had a polar origin, and otherwise (decrease in the APV) the air mass has an equatorial origin. As described above, the APV acts as a dynamic marker for large-scale air masses and, thus, observations are made to identify the secondary effect of AOH, where reductions in O 3 content are observed from intense to moderate (Bittencourt et al, 2018;Peres, 2016).…”
Section: Identification Of Aoh Influence Eventsmentioning
confidence: 99%
See 2 more Smart Citations